Synthesizing geovalent adjustment model for outward foreign direct investment performance among Malaysian medium-sized firms / Azman Mohd Isa - Mohd Isa, Azman (2018)
Outward Foreign Direct Investment (OFDI) activities have mainly been studied for Multi National Corporations (MNCs) but lesser for Small-Medium Enterprises (SMEs). This study shall make use of Geovalent Adjustment model introduced by Stephen Guisinger in 2001 as pedestal in analyzing the multi-faceted concepts of OFDI-related theories and Internationalization theories; in hope for finding similarities between the two. This study shall specifically make use of Malaysian Medium-sized firms as sample object for which they are already matured, both in terms of business operations as well as financial standings. This study hypothesizes that any similarities found from the said two foundational theories, could be synthesized into becoming one model, which would then provide an ease ground for medium-sized firms to adopt and practice. This study examines the Internal Business Processes (BP) of Malaysian medium-sized firms and international factors which Gusinger (2001) termed it as Geovalent Components (GC), for its influence on OFDI Performance (OP); and determines the mediator role of Geovalent Adjustment (GA) variable on the relationship between Business Process (BP) and Geovalent Components (GC) against OFDI Performance (OP). A survey was administered for Medium-sized firms which represented by senior management of those firms, for the whole of West Malaysia. Data generated was based on 124 of those senior management's self-rating of BP, GC, GA and OP. Rasch Model and SPSS programs were employed to analyze the data using several different analyses. Multiple regression, hierarchical stepwise regression, One Way ANOVA and Process were used to test the hypotheses. The results provided general support for five out of the five hypotheses. Specifically, the mediating effect of GA on the two independent variables of BP and GC against dependent variable of OP. This result confirms the earlier work of Guisinger (2001) which stated that GA is a must for any firms to internationalize or embarking on OFDI. Subsequently, the Rasch Model has developed a new OFDI Performance Measure (OPM) by generating 10 classifications of Malaysian Medium-sized firms. As this is a fresh finding, it serves as a new contribution for the present study. The results suggested that Business Processes (BP) and the international environment factors of Geovalent Components (GC) must be Geovalently Adjusted (GA) in order to influence OFDI Performance (OP) of Malaysian Medium-sized firms. Therefore, the Malaysian government needs to provide this synthesized model to Malaysian Medium-sized firms via testing and training mechanism introduced in this model, to increase the number of Malaysian Multinational Corporations (MNCs) quicker and more rapid. This is particularly important for Malaysian Medium-sized firms which generally focus their business operations on import-export base and neglecting the beneficial factors of investing abroad. Despite the new OFDI Performance Measure is an important contributions that should be replicated in other countries to confirm on the applicability of the measure, future researches need to look into more details and provide specific conceptualization of construct for the latent variable of Geovalent Adjustment.